Comparative evaluation of non enzymatic antioxidants, vitamin C and albumin in patients suffering from different grades of periodontitis: a retrospective observational study - Narendra, Suryakanta; Rath, Gayatri; Mohanty, Debasis; Jena, Sanghamitra (International Journal of Research in Medical Sciences, 2023)
Background: Rate of degree of destruction of periodontium may be associated with the oxidative stress due to the imbalance of different serum antioxidants. The objective of this study is to compare the evaluated concentrations of non enzymatic antioxidants like vit-C, albumin levels and total antioxidant status, from the available data of patients with slowly and rapidly progressive periodontitis (RPP). Methods: This retrospective observational study was confined to a study population, which include; 42 patients with RPP, 42 patients with slowly progressive periodontitis (SPP) and 86 healthy controls, in whom the required data were available. The levels of non enzymatic antioxidants like albumin, vitamin C and total antioxidant capacity (TAC) of patients, suffering from RPP, are compared with SPP and healthy controls. Results: The values of serum albumin and vitamin-c levels in RPP even remaining within the normal ranges were found to be on the lower side, when compared with healthy controls. The systemic TAC levels were found to be at a lower side in both SPP and RPP, when compared with the healthy control group. Conclusions: The systemic levels of non enzymatic antioxidants, vit C and albumin, in RPP were found to be on the lower side, even remaining within the normal ranges, when compared with the healthy controls. The TAC in SPP and RPP is also found to be on lower side, consistent with previous studies.